The Articulation of the Indigenous Peoples of Brazil in Facing the Covid-19 Pandemic - Silva, Luciana Leite da; Nascimento, Patrícia Emanuelle; Araújo, Ordália Cristina Gonçalves; Pereira, Tamiris Maia Gonçalves (Frontiers in Sociology, 2021)
This article aims to analyze how the indigenous communities of Brazil have organized autonomous actions and strategies to confront the Covid-19 pandemic based on the articulation among their own historical experiences, their health conceptions, partnerships with scientific communities and other segments of society that support the indigenous struggle. The research articulates the political and theoretical modernity/coloniality/decoloniality movement with indigenous experiences and conceptions of health, body/spirituality and territory. For this task, we adopted an undisciplined methodology based on conversation, solidarity and analysis of discussions, sites, lives, bibliographic productions and official documents prepared by indigenous organizations and partner entities. The research has pointed out that the situation of greater vulnerability of indigenous populations is not only due to biological factors. Also, indigenous people have denounced the invasion of their territories, racism, the lack of sanitation policies, food insecurity, the circulation of people not belonging to the community (missionaries, miners, loggers, army), the difficult access to hospitals and the precariousness of the necessary resources for individual and collective asepsis have worsen the spread and lethality of the virus. Likewise the current indigenous struggle in this pandemic scenario, this article is not limited to a health discussion, yet it aims to contribute to think about the relationship between the pandemic and the dissemination of anti-democratic policies that simultaneously affect the right to health and the territory of these populations.